Nucleobindin 2 expression is an independent prognostic factor for bladder cancer. Issue 13 (March 2020) - Cho, Jeong Man; Moon, Kyong Tae; Lee, Ho Jung; Shin, Soon Cheol; Choi, Jae Duck; Kang, Jeong Yoon; Yoo, Tag Keun
Abstract : Abstract: Nucleobindin 2 (NUCB2) has been reported to play an important role in both tumorigenesis and cancer progression. This study aimed to examine the clinical significance of NUCB2 expression urothelial carcinoma of the bladder (UCB). The expression level of NUCB2 and its correlation with clinicopathological parameters was analyzed in 225 UCB tissues by immunohistochemistry. Kaplan–Meier analysis and Cox proportional hazards regression models were used to investigate the correlation between NUCB2 expression and the prognosis of UCB patients. High NUCB2 expression of UCB patients significantly correlated with aggressive clinicopathological features. Patients with high NUCB2 had shorter overall survival and recurrence-free survival in Kaplan–Meier survival curve ( P  = .018 and P  = .001, respectively). Our results show that high expression of NUCB2 associated with aggressive clinicopathological feature and predicted unfavorable prognosis in patients with UCB might serve as feasible biomarker for clinical outcome of UCB patients after surgery and potential therapeutic target in the future.